CONTROL OF BLACK APHID (ALPHIS CRACCIVORA) IN COWPEA (VIGNA UNGUICULATA (L.) WALP WITH THE USE OF NEEM EXTRACT AND MANIPUEIRA - Santos, Jerffeson Leite; Barbosa, Douglas Rafael e Silva; da Silva, Giovana Lopes; Marques, Izaias Santos; Silva, Gutierres Nelson; Mendes, Elton Guimarães Rios; Rojas, Mariano Oscar Anibal Ibanez; Rima, Fernando Braga; Martins, Herus Pablo Firmino; da Silva, Erika Pereira; da Silva, Elias Ferreira; Morais, Victório Alessandro de Leão Loeschke (Seven Editora, 2025)
The black aphid Aphis craccivora Koch (Hemiptera: Aphididae) is pointed out as one of the main pests of cowpea, causing injuries through the suction of sap on the plants.  Conventional control involves the use of systemic chemical pesticides, which, from indiscriminate use, can cause contamination of the environment, applicators and other people, causing the selection of resistant insect populations. In view of this scenario, this study proposes to evaluate the toxicity, repellency and impact on population growth of A. craccivora when exposed to neem and manipueira extract. Leaf discs of cowpea plants were made, which were immersed in the concentrations of extract and volume of cassava, using the residual effect methodology for these experiments. Toxicity tests were performed to determine the sublethal concentrations LC20 and LC30 of neem extract and manipueira volume. In addition, tests were conducted to evaluate the repellency of the treatments, observing the behavior of the insects in relation to the previously determined concentrations. The study also analyzed the impact of the lethal concentration (CL) of neem extract and cassava extract on the population growth of A. craccivora, calculating the growth rate of the insect. The results showed that neem has a higher lethal concentration, both in LC50 and LC90, showing to be more toxic, with 0.99 times and 1.69 times, compared to cassava, in relation to the repellent effect, only neem in CL30 was repellent, while in the other concentrations, LC20 of neem itself and CL20 and LC30 of manipueira,  had a neutral classification. In the population growth the CL20  concentrations of neem and manipueira extracts there was no difference, however, it was evident that manipueira has a higher population growth rate in relation to neem.DOI: https://doi.org/10.56238/sevened2025.018-041